School Costs Are Rising and Massachusetts Vitally Needs Long-Range Planning for School Construction - Collins, George J.; Massachusetts State Dept. of Education, Boston ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
There is strong evidence which shows many communities have failed to plan adequately or even plan for long range school construction needs. This paper deplores this failure and gives some recommendations for long range planning. A checklist is described which may serve as a guide for conducting a school plant survey to identify and survey unmet educational needs, establish priorities, and provide for corrective action. Revisions and adjustments are stated to be a continual process. Community specifics can be studied, community planners coordinated, long range plans for school site acquisitions developed, and long range construction and operating budgets adopted. (NI)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Check Lists; Community Study; Community Surveys; Educational Needs; Educational Planning; Educational Programs; School Buildings; School Planning; School Surveys; Site Development